Ação da terapia fotodinâmica antimicrobiana com led vermelho na redução da halitose: ensaio clínico controlado - Ciarcia, Ana Carolina Costa da Mota (2018)
Halitosis is the term used to describe any unpleasant odor relative to expired air. The prevalence of halitosis in the population is approximately 30%, of which 80-90% of the cases originate in the oral cavity resulting from proteolytic degradation by gram negative anaerobic bacteria. Antimicrobial photodynamic therapy (aPDT) has been widely used and with quite satisfactory results in the health sciences, it involves the use of a non-toxic dye, called photosensitizer (PS), and a light source of a specific wavelength in the presence of the oxygen in the medium. This interaction can create toxic species that generate cell death. In view of the above, the objective of this controlled clinical study was to verify the effect of aPDT in the treatment of halitosis by the evaluation of the formation of volatile sulfur compounds with gas chromatography. Thirty-fi ve young adults aged 18 to 25 years, with gas chromatographic halitosis were included in the study. The selected subjects were divided into 3 groups, G1 aPDT with 0.005% methylene blue with red LED 660nm, 4 irradiation points, 90s per point, 400mW of power, 36J per point, G2 Scraper and G3 Scraper and aPDT. All subjects underwent Oral ChromaTM evaluation before, after treatment and controls of 7, 14, 30. Wilcoxon test was used for the analysis of data from Oral ChromaTM intragroup and for the intergroup analysis the Kruskal Wallis test. A significance level of 95% (p <0.05) was considered for all analyzes. It was possible to observe statistically significant difference immediately after treatment for all groups, but the result was not maintained after 7 days.